Polyamine Binding Studies with Silk gland and Testicular DNA of Bombyx mori. L (Lepidoptera: Bombycidae) - Mysarla, Danti Kumari; Yerra, Aparna; Mamillapalli, Anitha (Asian Journal of Biological and Life Sciences, 2016)
Silkworms synthesize silk from the beginning of larval stages but, predominant production takes place during 5th instar larval stage. Silk is produced by a specialized organ of silkworms called as silk gland. Silk production and fecundity play a very important role in sericulture industry. Polyamines are low molecular weight polycations present in all living cells and proved to be regulators for growth and cell survival. Many studies have shown binding of polyamines to DNA. In the present study we investigated DNA binding efficiency of spermidine and spermine with silk gland DNA and testicular DNA taking calf thymus DNA as control. Results showed that both the polyamines caused hypochromic shift to the silk gland and testicular DNA similar to calf thymus DNA. The hypochromic effect increased with increase in the concentration of the polyamine. Moreover, spermine was better than spermidine in binding to DNA. In the presence of spermidine and spermine, melting temperatures of silk gland and testicular DNA increased more than calf thymus DNA. Thus the study shows binding of polyamines to silk gland and testicular DNA is similar to their binding to calf thymus DNA and cause DNA condensation.
Keywords: DNA binding; Silk gland; Silkworm; Spermidine; Spermine; Testis